Risk of obstructive sleep apnea and hemodialysis efficacy - Mahnaz Amini; Fereshteh Roohafza; Fatemeh Nazemian; Negar Morovatdar; Asieh Hatefi olaee (Journal of Nephropathology, 2018)
Background: Obstructive sleep apnea (OSA) occurs frequently in hemodialysis (HD) patients with important consequences and increased mortality. However the role of adequacy of HD on the prevalence of OSA is less studied. Objectives: Our aim was to screen OSA and evaluate the effect of HD adequacy on the risk of OSA. Patients and Methods: This is a cross-sectional study on adult HD patients. Clinical and laboratory parameters were collected. The risk of OSA was assessed by STOP-BANG and Berlin questionnaire (BQ). Excessive daytime sleepiness (EDS) was evaluated with Epworth Sleepiness Scale (ESS). Kt/V index was applied for determining HD adequacy. Mortality followed after 2 years. Results: Sixty-five patients (63% men, with a mean age of 53±16.5 years) were included in the study. Most of the subjects were categorized as high risk by Berlin (68.3%) and STOPBANG (84.6%) questionnaires and 25.8% had EDS. Participants who were categorized as high risk of OSA showed lower Kt/V (P=0.018 based on BQ, P=0.002 based on STOPBANG). OSA risk was significantly correlated with Kt/V (OR: 0.007; CI: 0-0.36; p: 0.01). Two-year mortality was not significantly correlated with OSA. Conclusion: OSA was prevalent in our HD patients and correlated with less adequacy of HD. Screening for this common disease by nephrologists using simple questionnaires is recommended.